1989
DOI: 10.1508/cytologia.54.27
|View full text |Cite
|
Sign up to set email alerts
|

Interphase nuclear structure and heterochromatin in Cicer species.

Abstract: Interphase nuclear structure has been investigated using various techniques of light , phase contrast, fluorescence and electron microscopy . These studies have indicated several interest ing features of the interphase nuclei (once thought to be resting nucleus) like non -random ar rangement of chromosomes, somatic association and specific orientation of chromosomes maintaining their telophasic configurations (Patankar and Ranjekar 1984) . Interphase nuclear organization of plants is species specific , however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Similar type of re sults were reported in Cicer by Kabir and Singh (1989). Nagl (1979) has suggested that in plants, the variation in the proportion of heterochromatin between meristematic and differentiat ed cells can serve as an indication of differential DNA replications.…”
Section: Insupporting
confidence: 75%
See 1 more Smart Citation
“…Similar type of re sults were reported in Cicer by Kabir and Singh (1989). Nagl (1979) has suggested that in plants, the variation in the proportion of heterochromatin between meristematic and differentiat ed cells can serve as an indication of differential DNA replications.…”
Section: Insupporting
confidence: 75%
“…Chromocentre numbers in two species of Corchorus and their hybrid were more or less same, which were, however, found to reduce than the expected number of 14. This might be due fusion or overlapping of chro mocentres indicating the somatic association of chromosomes (Kabir and Singh 1989). The number of chromocentres in the nuclei of F, was found to be somewhat closer to the male parent than that of the female parent.…”
Section: Methodsmentioning
confidence: 84%
“…(KABIR and SINGH 1989). The close proximity of some of these prochrosomes to each other in Vanilla planifolia might be indicating the initiation of somatic association even in interphase.…”
Section: Discussionmentioning
confidence: 97%
“…All interphase nuclei of giant cells and several nuclei of syncytia contained more than the expected number of 10 chromocenters. Chromocenters were also larger than those in nuclei of neighboring cells, probably because of overlapping, fusion, or polyteny (Kabir and Singh, 1989). A detailed confocal analysis of these nuclei will reveal whether somatic association of chromosomes and/or polyploidy occurs in nuclei of feeding cells.…”
Section: Dna Synthesis In Galls and Syncytiamentioning
confidence: 97%